Bibliometric analysis of climate research in East Africa: The rise and progress - Mohammed Rady; Ahmed Abdiaziz Alasow; Abdifatah Ahmed Hersi (Sustainable Environment)
East Africa’s diverse ecosystems and socio-economic vulnerabilities make it susceptible to climate challenges. Despite a growing body of climate research in the region, a comprehensive analysis of its current state and key themes has been lacking. This study aims to address this gap by conducting a bibliometric analysis of climate research in East Africa from 2000 to 2024. The specific objectives of this research are to examine publication trends and patterns in East African climate research, explore thematic focus areas across different disciplines, and assess the regional distribution of climate research efforts. Using the Scopus database, the authors identified and analyzed 5064 relevant publications across 13 East African countries. The results reveal a significant increase in the climate research over the past decade, with annual publications rising by over 500%. Ethiopia was the leading contributor, accounting for more than one-third of all publications, followed by Kenya and Tanzania. In contrast, Seychelles and Comoros collectively contributed only 1% of the region’s climate research. The analysis also highlighted significant international collaboration, with non-African countries such as the US, UK, and Germany among the top five contributing nations. The top key subject areas included environmental sciences, earth and planetary sciences, agricultural and biological sciences, and social sciences. The outcomes of this analysis could assist scholars and policymakers in developing climate research in the region by highlighting areas of strength and identifying regions that require further attention.